2012
DOI: 10.1177/193229681200600220
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Fascia Thickness is Longitudinally Associated with Retinopathy and Renal Dysfunction: A Prospective Study from Adolescence to Adulthood

Abstract: Abbreviations: (AER) albumin excretion rate, (AGE) advanced glycation end product, (BMI) body mass index, (DBP) diastolic blood pressure, (DCCT) Diabetes Control and Complications Trial, (GEE) generalized estimating equations, (HbA1c) glycated hemoglobin, (MA) microalbuminuria, (MV) microvascular, (OR) odds ratio, (ORPS) Oxford Regional Prospective Study, (PFT) plantar fascia thickness, (RAGE) advanced glycation end product receptors, (SBP) systolic blood pressure, (SD) standard deviation, (SDS) standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Some studies have found that the thickness and stiffness of the PF and Achilles tendon are increased in patients with type I and type II diabetes mellitus [37, 38]. PF thickness is considered a predictor of the development of late complications in type I diabetes mellitus [38, 39]. Moreover, a relationship between PF thickening in type II diabetes mellitus and body mass index values has also been demonstrated [37].…”
Section: General Features Of Pf Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that the thickness and stiffness of the PF and Achilles tendon are increased in patients with type I and type II diabetes mellitus [37, 38]. PF thickness is considered a predictor of the development of late complications in type I diabetes mellitus [38, 39]. Moreover, a relationship between PF thickening in type II diabetes mellitus and body mass index values has also been demonstrated [37].…”
Section: General Features Of Pf Disordersmentioning
confidence: 99%
“…Increased thickness of the PF can be sonographically detected in the early stages of diabetes mellitus [3739]. Ultrasound can aid in the diagnosis of foreign body reaction by identifying echoic extraneous material within or adjacent to the PF.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Diabetes is associated with overall thickening and stiffness of the main tendons and ligaments of the foot-ankle complex, i.e. the plantar fascia (PF) and Achilles tendon (AT) [ 132 - 135 ].…”
Section: Joint Mobilitymentioning
confidence: 99%
“…It has been reported that the PF thickness is a measure of tissue glycation and it is longitudinally associated to the development of complications in type 1 diabetes mellitus patients [ 135 , 136 ].…”
Section: Joint Mobilitymentioning
confidence: 99%
“…During the last decades, studies have found numerous biomarkers, such as HbA 1c [4446], skin collagen glycation [15], plantar fascia thickness [47], AGEs [48,49], oxidized low-density lipoprotein (oxLDL) [49], nitric oxide metabolic pathway products (NOx) [49], as well as H3K9 acetylation in monocyte [17], to predict the progression of diabetic vascular complications and the occurrence of metabolic memory. Recently, circulating microRNAs have been associated with diabetes and its vascular complications [50].…”
Section: Clinical Perspectives and Future Implicationsmentioning
confidence: 99%